2017
DOI: 10.1007/s13300-017-0274-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Additional Canagliflozin Administration to Type 2 Diabetes Patients Receiving Insulin Therapy: Examination of Diurnal Glycemic Patterns Using Continuous Glucose Monitoring (CGM)

Abstract: IntroductionThe efficacy of administering a sodium–glucose cotransporter 2 inhibitor during insulin therapy has not been established. In this study, we examined its effects based on diurnal glycemic patterns using continuous glucose monitoring (CGM).MethodsThe subjects were 15 patients who had received insulin therapy for 1 year or more. A CGM device was attached to all subjects for 1 week. The administration of canagliflozin at 100 mg was started 4 days after attachment. The mean glucose concentrations, stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
8
21
0
1
Order By: Relevance
“…Thus, the ability of canagliflozin treatment to increase adiponectin independent of weight loss or improvements in glycemia, together with a decrease in leptin and IL-6, may be indicative of a primary improvement in adipose tissue function with direct implications related to metabolic health. Of note, increases in adiponectin have recently been seen with canagliflozin treatment (100 mg dose) in a small study of patients with type 2 diabetes on background insulin [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the ability of canagliflozin treatment to increase adiponectin independent of weight loss or improvements in glycemia, together with a decrease in leptin and IL-6, may be indicative of a primary improvement in adipose tissue function with direct implications related to metabolic health. Of note, increases in adiponectin have recently been seen with canagliflozin treatment (100 mg dose) in a small study of patients with type 2 diabetes on background insulin [22].…”
Section: Discussionmentioning
confidence: 98%
“…Certain adipokines, pro-inflammatory cytokines, and chemokines regulate adipose tissue function and metabolic processes that contribute to cardiovascular risk in patients with type 2 diabetes and obesity. While studies have shown that treatment with glimepiride is not associated with meaningful changes in most of these biomarkers [18,19], there is some limited evidence to suggest that SGLT2 inhibitors may have favorable effects on serum leptin, adiponectin, IL-6, TNFα, CRP, and MCP-1 levels [9,[20][21][22]. Our analyses were the first to assess changes in adipokines, inflammatory biomarkers, and chemokines based on data from a large, randomly selected subset of patients with type 2 diabetes enrolled in an active-controlled trial [14].…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al reported that glinide treatment was more beneficial than SU for decreasing daily glucose variability; comparisons were also made to determine the effects of glinide and SU treatments on oxidative stress [32]. Recent studies have reported that SGLT2 inhibitors, which decrease plasma glucose levels in an insulin-independent manner by selectively inhibiting renal glucose reabsorption and increasing urinary glucose excretion, improved daily and day-to-day glucose variability and reduced oxidative stress [33]. Although improvement of glucose variability is important for reducing oxidative stress, treatment of glucose variability without stimulating insulin secretion may be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Although previously it was difficult to clarify at which point within a 24-h time frame the effects of such drugs were exerted, this information has become clear with the advent of the CGM system. This system allows greater ease in determining the effects of existing drugs and the effect of additional administration of other anti-diabetes drugs [ 26 , 27 ]. Furthermore, detection of hypoglycemia related to CV events has become possible [ 10 , 28 , 29 ].…”
Section: Short-term Glycemic Variabilitymentioning
confidence: 99%